Small-angle X-ray scattering from wet gels prepared from co-hydrolysis of tetraethoxysilane and vinyltriethoxysilane - Donatti, Dario A. [UNESP]; Ruiz, Alberto Ibanez [UNESP]; Vicelli, Marcio R. [UNESP]; Vollet, Dimas R. [UNESP] (Springer, 2009)
Small-angle X-ray scattering was used to study the structure of wet gels prepared from co-hydrolysis of tetraethoxysilane (TEOS) and vinyltriethoxysilane (VTES) in the VTES/(VTES + TEOS) molar ratio ranging from 0 to 1. The wet gels at pH = 6 behave as a mass-fractal structure with characteristic size xi and fractal dimension D, both increasing with the amount of VTES from xi = 6.78 nm and D = 2.25 for pure TEOS until an almost homogenous structure with xi similar to 24.9 nm and D similar to 2.85 is obtained for the wet gel prepared with pure VTES. The mass-fractal structures are built up by small primary clusters of characteristic size between similar to 0.35 and similar to 0.85 nm, the size increasing with the quantity of VTES. These small particles of the gels are formed by a restructuring process of a few larger macromolecules in the stable sols (pH = 2) on passing from the acid to the increased-pH step of the process.
Keywords: SAXS; TEOS-VTES; Co-hydrolysis; Mass fractal